Radiation dose uncertainty and correction for a mouse orthotopic and xenograft irradiation model. (2nd January 2016) - Gan, Gregory N.; Altunbas, Cem; Morton, John J.; Eagles, Justin; Backus, Jennifer; Dzingle, Wayne; Raben, David; Jimeno, Antonio
Abstract: Purpose In animal irradiation models, reported dose can vary significantly from the actual doses delivered. We describe an effective method for in vivo dose verification. Materials and methods Mice bearing commercially-available cell line or patient-derived tumor cell orthotopic or flank xenografts were irradiated using a 160 kVp, 25 mA X-ray source. Entrance dose was evaluated using optically-stimulated luminescence dosimeters (OSLD) and exit dose was assessed using radiochromic film dosimetry. Results Tumor position within the irradiation field was validated using external fiducial markers. The average entrance dose in orthotopic tumors from 10 OSLDs placed on two different animal irradiation days was 514 ± 37 cGy (range: 437–545). Exit dose measurements taken from seven radiochromic films on two separate days were 341 ± 21 cGy (a 34% attenuation). Flank tumor irradiation doses measured by OSLD were 368 ± 9 cGy compared to exit doses of 330 cGy measured by radiochromic film. Conclusion Variations related to the irradiation model can lead to significant under or overdosing in vivo which can affect tumor control and/or biologic endpoints that are dose-dependent. We recommend that dose measurements be determined empirically based on the mouse model and irradiator used and dose compensation adjustments performed to ensure correct and appropriate doses.